2018
DOI: 10.21608/jpp.2018.36634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Source and Rates on Grain Yield, Morphological and Physiological Traits of some Maize Hybrids

Abstract: A field experiment was carried out in old newly reclaimed calcareous soils at Nubaria Agricultural Research Station, during 2015 and 2016 summer seasons. The aim of the investigation was to study the effect of nitrogen fertilizer sources (solid and gaseous) under different nitrogen rates (80, 100, 120 and 140 kg N fed-1) on yield, yield components, NPK concentrations and N use efficiency for some maize hybrids (SC 131, SC 168 and SC 176). Experimental design was strip-split plot design with four replications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…This is to be expected since such genotype recorded the highest values of stem and total dry weight/ plant as recorded in Table 3. These results were coincided by those obtained by Ali (2016), Balbaa & Awad (2018), Darwich (2018) and Mostafa (2018) who reported that yellow maize genotype namely S.C 168 was superior to other tested genotypes in grain yield/ fed.…”
Section: Yields/ Fed and Translocation Indicessupporting
confidence: 88%
See 2 more Smart Citations
“…This is to be expected since such genotype recorded the highest values of stem and total dry weight/ plant as recorded in Table 3. These results were coincided by those obtained by Ali (2016), Balbaa & Awad (2018), Darwich (2018) and Mostafa (2018) who reported that yellow maize genotype namely S.C 168 was superior to other tested genotypes in grain yield/ fed.…”
Section: Yields/ Fed and Translocation Indicessupporting
confidence: 88%
“…However, no significant variations were detected in oil % among all tested genotypes in both seasons. The differences among some yellow maize genotypes were also previously reported by many investigators such as Balbaa & Awad (2018) and Mostafa (2018) for protein percentage as well as Mreer & Mohamad (2017) for oil yield/ unit area.…”
Section: Grain Qualitysupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, dust accumulation can also reduce the plant's retention and uptake of the herbicide 13,25 . The TCC indicates the plant's photosynthetic activity 53 and can be affected by the herbicide's mode of action 54 .…”
Section: Total Chlorophyll Content (Tcc)mentioning
confidence: 99%
“…Current studies [7][8][9] show that adverse environmental conditions, such as drought and extreme heat, caused by climate change, can indirectly lead to other environmental problems, e.g., the dispersal of airborne dust to different parts of the world. In recent years, the issue of dust has become a central concern in Middle Eastern countries, including Iran and Iraq [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%